2011
DOI: 10.1038/bcj.2011.38
|View full text |Cite
|
Sign up to set email alerts
|

Redeployment-based drug screening identifies the anti-helminthic niclosamide as anti-myeloma therapy that also reduces free light chain production

Abstract: Despite recent therapeutic advancements, multiple myeloma (MM) remains incurable and new therapies are needed, especially for the treatment of elderly and relapsed/refractory patients. We have screened a panel of 100 off-patent licensed oral drugs for anti-myeloma activity and identified niclosamide, an anti-helminthic. Niclosamide, at clinically achievable non-toxic concentrations, killed MM cell lines and primary MM cells as efficiently as or better than standard chemotherapy and existing anti-myeloma drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 53 publications
2
79
0
15
Order By: Relevance
“…A wide range of RTKs phosphorylate STAT3 directly or via SRC kinase, and several studies have proven that blocking kinases such as KDR, PDGFRB, and ALK results in enhanced autophagy by subsequent inhibition of the STAT3 pathway (Table 3). 14,41,42,50,[74][75][76][77][78][79][80][81][82][83] Currently, several JAK-STAT inhibitors are being examined in clinical trials for cancer therapy. For example, in a phase II clinical trial to treat metastatic pancreatic cancer, ruxolitinib together with capecitabine showed a benefit for overall survival and progression-free survival compared with a placebo plus capecitabine used in second-line therapy, promoting the application of JAK-STAT inhibitors in cancer therapy.…”
Section: Implication Of Stat3-regulated Autophagy In Cancer Therapeuticsmentioning
confidence: 99%
“…A wide range of RTKs phosphorylate STAT3 directly or via SRC kinase, and several studies have proven that blocking kinases such as KDR, PDGFRB, and ALK results in enhanced autophagy by subsequent inhibition of the STAT3 pathway (Table 3). 14,41,42,50,[74][75][76][77][78][79][80][81][82][83] Currently, several JAK-STAT inhibitors are being examined in clinical trials for cancer therapy. For example, in a phase II clinical trial to treat metastatic pancreatic cancer, ruxolitinib together with capecitabine showed a benefit for overall survival and progression-free survival compared with a placebo plus capecitabine used in second-line therapy, promoting the application of JAK-STAT inhibitors in cancer therapy.…”
Section: Implication Of Stat3-regulated Autophagy In Cancer Therapeuticsmentioning
confidence: 99%
“…It seems that inhibition by niclosamide occurs at a post-entry step, such as replication [40,41]. Niclosamide is a category B drug, which indicates that no risk to fetuses has been found in animal studies due to its low toxicity in mammals [42]. The WHO recommends that niclosamide may be used during pregnancy because it has not been shown to be mutagenic, teratogenic or embryotoxic [43].…”
Section: Niclosamidementioning
confidence: 99%
“…Для поиска новых препаратов, которые были бы эффективны для лечения миеломной болезни, Khanim и соавт. провели скрининг более 100 известных препаратов с разной терапевтической специфичностью для выявления соединений, обладающих цитотоксической активностью в той концентрации, которая достигается в сыворотке крови при их клиническом применении, в отношении трёх линий клеток миеломы человека [17]. В результате такого скрининга высокая активность в отношении клеток миеломы была обнаружена у никлозамида.…”
Section: множественная миеломаunclassified
“…Исследуя механизм действия никлозамида, авторы показали, что он способен индуцировать образование АМК, в том числе, супероксидного аниона (СОКС) в митохондриях клеток множественной миеломы человека [17].…”
Section: множественная миеломаunclassified
See 1 more Smart Citation